A collective call to strengthen monitoring and evaluation efforts to support healthy and sustainable food systems: 'The Accountability Pact'. Issue 9 (16th September 2022) - Garton, Kelly; Kraak, Vivica; Fanzo, Jessica; Sacks, Gary; Vandevijvere, Stefanie; Haddad, Lawrence; Brinsden, Hannah; Laar, Amos; Karupaiah, Tilakavati; Omidvar, Nasrin; Masters, William; Kauer, Inge; et al.
Abstract: There is widespread agreement among experts that a fundamental reorientation of global, regional, national and local food systems is needed to achieve the UN Sustainable Development Goals Agenda and address the linked challenges of undernutrition, obesity and climate change described as the Global Syndemic. Recognising the urgency of this imperative, a wide range of global stakeholders – governments, civil society, academia, agri-food industry, business leaders and donors – convened at the September 2021 UN Food Systems Summit to coordinate numerous statements, commitments and declarations for action to transform food systems. As the dust settles, how will they be pieced together, how will governments and food corporations be held to account and by whom? New data, analytical methods and global coalitions have created an opportunity and a need for those working in food systems monitoring to scale up and connect their efforts in order to inform and strengthen accountability actions for food systems. To this end, we present – and encourage stakeholders to join or support – an Accountability Pact to catalyse an evidence-informed transformation of current food systems to promote human and ecological health and wellbeing, social equity and economic prosperity.